Impact of Shatavari (Asparagus racemosus) Root Meal Supplementation on Growth Performance, Haematology and Carcass Quality of Broiler Chickens - Verma, Raj Kapoor; Pramanik, Partha Sarathi; Singh, Kunwar Dhananjay; Verma, Ajeet Kumar; Singh, Shailendra; Kumar, Abhishek; Gupta, Nitish (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The goal of this study was to evaluate the effects of Shatavari (Asparagus racemosus) root meal supplementation on the growth, haematology and carcass quality of broiler chickens. Two hundred day-old chicks (Vencobb 400) were randomly divided into four groups with 50 chicks in each using two replicates each of 25 chicks under completely randomized design. Control group TC was fed commercial diet without Shatavari root powder, while group T1, T2 and T3 were fed commercial diet supplemented with 0.5%, 1.0 % and 1.5% Shatavari root powder, respectively, for 42 days. The results showed that T2 had the highest body weight (2547.76 g), followed by T1, TC and T3. The TC group exhibited the highest overall feed intake (4339.64 g), followed by T1, T2, and T3. At 42nd day of treatment, the mean Hb concentration of the T2, T3, and T1 groups of birds was considerably greater and TLC was lower (p<0.05) than TC group. Birds in the T2 group had considerably greater PCV% than those in the TC, T1, and T3 groups. For the groups TC, T1, T2, and T3, the H:L ratios were 0.47, 0.49, 0.54, and 0.52, respectively. Overall carcass characteristics were better in T2 group, regarding slaughter yield. The wing, neck and abdominal fat contents decreased significantly (p<0.05), while Giblet percent increased as the level of Shatavari root meal increased in the diet. Thus, it was inferred that the inclusion of 1% Shatavari (Asparagus racemosus) root powder supplementation in the commercial diet of broiler chickens improves growth performance, haematological parameters and carcass quality much better than higher or lower levels of Shatavari.